Environmental Impact Analysis on Chicken Embryo Development: A Systematic Review - Fadhli Rahman Fauzi; Maslichah Mafruchati (JURNAL RISET RUMPUN ILMU HEWANI, 2025)
Environmental stress can affect the development of the embryo, including causing the death of the embryo. Environmental factors that can cause stress include salinity and zinc sulfate, zinc sulphate is a trace element and can affect embryonic development. The purpose of this study was to analyze the environment in Chicken embryonic development. A literature search was carried out systematically through the PubMed, NCBI, Google Scholar databases using keywords, namely, “heat, stress, embryo, chicken”. Based on these keywords, the articles obtained were first selected by setting several inclusion criteria. Articles that do not meet the inclusion criteria are eliminated, and articles that meet the criteria will be analysed to obtain data. Based on the search results 21326 articles were obtained, and 21 articles that meet the inclusion criteria were selected. The result above also showed that heat stress give impact to development of embryo. From the results of the research conducted, it can be concluded that the environment has an impact on the development of the embryo. Further studies are needed, especially those related to other types of stress that can affect embryonic development in various types of animals.